HOW HAS COVID-19 CHANGED THE WAY HOSPITALS DELIVER CARE? - Ilham Akhsanu Ridlo (Universitas Airlangga, 2021)
During the pandemic, healthcare facilities in Indonesia faced very vulnerable conditions. So far, dealing with the pandemic has had a significant impact on the national referral system for health services. Hospitals are the last line of defence for the increase in COVID-19 referral cases, leading to high percentage of BOR (Bed Occupancy Rate). We have selected several articles related to health services, especially hospitals, to provide perspectives and contributions to different referral health services.